Do coaches believe they can predict athletes` responses to training? an international survey of coaches` beliefs regarding the predictability of training-induced adaptations - Anyadike-Danes, K.; Donath, L.; Kiely, J. (International Journal of Sports Science & Coaching, 2025)
The training process, as posited by periodization, is depicted as based on predictable phenomena. This survey investigated how coaches perceive the predictability of athletes` responses to training. A sample of 106 coaches [age range: 18-65 + years, 31% 15 + years coaching experience, 58% worked in individual-events/sports and 32% worked with athletes competing at international level] from various countries participated in an online survey regarding the predictability of training responses. Few coaches (13%) indicated that they could `Often` predict how much an athlete would improve over a training phase. When asked whether it was feasible to predict an athlete's response to either a single session, or a series of them, there was limited outright agreement (14% and 23%, respectively). The majority of coaches indicated that they made changes to the plan with many (46%) doing so frequently (`Always` and `Often`). A key assumption within traditional training theory is that training outcomes are predictable. The current results suggest that coaches may not believe this to be the case. Instead they may be more consistent with modern conceptualizations of the adaptation process as a complex system evolving over time. If training theory is to remain relevant and aid coaches then it needs to engage with these problems and the realities coaches face.